Ecological studies of Medium to large mammals in oil palm plantation, Miri, Sarawak - Lok, Lisa Choy Hong; Mohd. Azlan, Jayasilan (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Good or evil? Palm oil has always been in the centre of a decade long controversy. While it contributes to the economy, alleviates poverty and is by far the most land-efficient oil crop, it comes at the cost of local ecosystems and devastates lands which are highly biodiverse such as Borneo (Laurence et al., 2014). Approximately 12.5% of the land in Sarawak has already been converted to oil palm plantations (MPOB, 2017). Monocrops have proved to be much lower in biodiversity compared to forested areas as it lacks necessary resources for many species. Despite efforts from the Roundtable of Sustainable of Oil Palm (RSPO) to push for sustainable oil palm practices such as maintaining High Conservation Value Forest (HCVF), knowledge gaps on the effects of management practices towards the local fauna still exists and comprehension on the carrying capacities of the oil palm are still limited. It is therefore critical to conservation to figure out how to improve oil palm plantation to be more hospitable to wildlife. Among the most threatened taxonomic group due to fragmentation are mammals as they are highly sensitive to anthropogenic pervasion to and into their habitats. Medium to large mammals were selected as a focus group in this study as they are regarded as keystone species and are excellent bioindicators for healthy ecosystems. A one-year long camera trap survey of medium to large mammals is currently being conducted to provide baseline data on mammalian diversity and its persistence within the HCV forest fragments and oil palm matrix in regards to management practices for management decision. We have recorded various species of conservation importance in forest fragments. This includes the Sunda Pangolin (Manis javanica), Sun Bear (Helarctos malayanus) and Sambar Deer (Rusa unicolor). An adaptive management plan and integrated conservation strategy will be formulated at the end of the project to contribute to the preservation, sustenance and enhancement of the HCVF areas and in the oil palm areas.